POLITIK MENURUT FOUCAULT DALAM “THE ARCHAEOLOGY OF KNOWLEDGE” DAN RELEVANSINYA BAGI MULTIKULTURALISME INDONESIA - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2018)
Political science, the study of politics, examines the acquisition and application of power. Related areas of study include political philosophy, which seeks a rationale for politics and an ethic of public behavior, political economy, which attempts to develop understandings of the relationships between politics and the economy and the governance of the two, and public administration, which examines the practices of governance. Many have dream up the idealization of the politics realization. Politics should not dirty! But, the fact, actually in Indonesia, politics are corruption, abuse of power, and immoral. Is that only one paradigm of politics? Indonesia must learn to Foucault to build the good governance. Specially, i hope, the discussion of this theme can give any contribution for Indonesian politic and social lives, of which to be felt decline in any ways progressively.